Challenges of Goodwill Accounting: Including Chinese Goodwill Accounting - Wang, Yilin (2008)
Nowadays, with the fast development of economy goodwill has become an important intangible asset in the accounting. Goodwill has significant effects on both survival and development of the enterprise. Studying on goodwill accounting can help users with using accounting information, especially users of the outside of the enterprise to understand the real value of an enterprise. This can help an enterprise to use resources adequately and can increase the competitive capability of an enterprise on international market.